Deposition of YTTRIA stabilized zirconia thin films by radio frequency magnetron sputtering for solid oxide fuel cell - Jaffar, Siti Noryasmin (2017)
Yttria stabilized zirconia (YSZ), the most significant material of electrolytes in solid oxide fuel cell (SOFC) requires careful synthesis and thorough characterizations with improved properties. Presently, YSZ electrolytes are largely manufactured by screen printing or spraying techniques followed with subsequent sintering. Despite their low-cost with high throughput, these techniques cannot produce dense YSZ electrolytes thin film of thickness with nanometer size. In this research, this problem was resolved by depositing dense YSZ electrolyte thin film with good electrical properties through radio frequency (RF) magnetron sputtering (RFMS) technique. YSZ thin films were successfully deposited on alumina (Al2O3) substrate through reactive RFMS technique. The formation of fully dense and highly porous films for efficient SOFC fabrication is dependent upon deposition parameters of RFMS such as gas pressure, deposition power and rate, substrate temperature and sputtering time. Pure nanostructured YSZ thin films were prepared in the atmosphere of mixed argon and oxygen gas. To optimize the YSZ film properties, deposition parameters such as RF power, substrate and annealing temperature were varied. Samples were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) spectroscopy, atomic force microscopy (AFM), surface profiler, and four point probe analysis. XRD spectra revealed the growth of Zr-Y-O nanocrystallites along the lattice plane of (220) and (111), where the average crystallite size increased from 24.81 nm to 68.56 nm with the increase of RF power. The FESEM images displayed the homogeneous surface morphology of the deposited YSZ thin film. Meanwhile, the AFM topological analysis showed an increase in grain size from 26.29 nm to 76.41 nm and that surface roughness was reduced from 3.28 nm to 1.67 nm with increasing RF power from 50W to 150W. The resistivity of YSZ films was reduced from 745 O.cm to 1.33 O.cm with the increase of substrate temperature from 37°C to 500°C. Furthermore, the resistivity of the film was diminished with the decrease of YSZ thin film thickness from 66.08 nm to 8.25 nm. RF power of 100W and substrate temperature of 300°C was shown as the optimum parameter for depositing nanostructured YSZ thin films. The findings have proven that by lowering the thickness of nanostructured YSZ thin film deposited with substrate temperature of 500°C or less, an optimum film can be achieved. Overall, the present findings may contribute towards the development of YSZ thin film based electrolytes beneficial for SOFC.